The Implementation of Reflective Pedagogy in Advanced Critical Reading and Writing Class - Suminto, Elisabeth Avryanne; Ena, Ouda Teda (Language Circle: Journal of Language and Literature, 2020)
Reflective pedagogy is a method dealing with a teaching methodology which is done based on a certain spiritualilty. It is important to study the implementation of reflective pedagogy because it helps the students to excel as fully human persons who own competence, compassion, and conscience. This study observes the implementation of reflective pedagogy in Advanced Reading and Writing Class. This research aims to find out the perceptions of the students on the process and the effects of the implementation. The writers employed survey to collect the data. The findings revealed that in general, the students had positive perceptions on the process and the effects of implementing Reflective pedagogy in Advanced Critical Reading and Writing class. The implementation of reflective pedagogy had been successful in developing students’ competence, conscience, and compassion. However, based on the interview, students’ conscience was developed to a limited extent.